2017
DOI: 10.5826/dpc.0704a08
|View full text |Cite
|
Sign up to set email alerts
|

Diet and rosacea: the role of dietary change in the management of rosacea

Abstract: Dietary change may play a role in the therapy of rosacea. Certain foods and beverages may act as “triggers” for rosacea exacerbations. These may be divided into heat-related, alcohol-related, capsaicin-related, and cinnamaldehyde-related. One potential pathogenic mechanism may be via the activation of transient receptor potential cation channels, which result in neurogenic vasodilatation. Further research is needed on the role of the gut skin connection in rosacea. Epidemiologic studies suggest that patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 63 publications
(73 reference statements)
0
54
1
1
Order By: Relevance
“…For example, alcoholic beverages, spicy food, hot drinks, and chocolate are well-known dietary triggers of rosacea. Diet has a substantial impact on the regulation of the human microbiome [ 72 ] and dysbiosis in the intestine has a negative impact on skin function. Metabolites of the microbiota could accumulate in the skin and thereafter damage the integrity of the skin barrier and promote further inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, alcoholic beverages, spicy food, hot drinks, and chocolate are well-known dietary triggers of rosacea. Diet has a substantial impact on the regulation of the human microbiome [ 72 ] and dysbiosis in the intestine has a negative impact on skin function. Metabolites of the microbiota could accumulate in the skin and thereafter damage the integrity of the skin barrier and promote further inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Among rosacea patients with SIBO prescribed rifaximin, 46% of the patients with rosacea reported cleared or marked improvement in their skin lesions [ 52 ]. The suggested pathomechanism involved in the association between rosacea and SIBO could be explained by increases in shared circulating cytokines, especially tumor necrosis factor-alpha [ 72 ]. However, a Danish population-based cohort study found no significant association between SIBO (HR: 0.71; 95% CI: 0.18–1.86) in patients with rosacea compared with control subjects [ 60 ].…”
Section: The Risk Of Gastrointestinal Disorders In Rosaceamentioning
confidence: 99%
“…The disease may present itself in the form of persisting erythema, telangiectasia, papules, pustules, excessive fibrous tissue overgrowth, rhinophyma and periocular changes . The role of the dietary habits emphasizes the importance of the gastrointestinal tract in the rosacea pathogenesis . Also specific microbiome changes are contributed to Toll‐like receptors abnormal activation observed in rosacea patients .…”
Section: Methodsmentioning
confidence: 99%
“…78 The role of the dietary habits emphasizes the importance of the gastrointestinal tract in the rosacea pathogenesis. 79 Also specific microbiome changes are contributed to Toll-like receptors abnormal activation observed in rosacea patients. 80 Rosacea is reported to coincide with gastrointestinal comorbidities and certain studies link this coexistence to gut microbiome changes.…”
Section: Rosaceamentioning
confidence: 99%
“…Anecdotally, many patients are affected by spices and hot condiments. Other trigger foods and drinks include tomatoes, citrus fruits, wine, and hard liquor . Hot coffee or tea may have a negative impact.…”
Section: Management Recommendationsmentioning
confidence: 99%